Review of 9 Cases of Diaphragmatic Injury Following Blunt Trauma Chest; 3 Years Experience - Nain, Prabhdeep Singh (Springer India, 2012)
Diaphragmatic injuries can occur with both blunt and penetrating trauma which can be associated with herniation of abdominal viscera into the thoracic cavity. Diaphragmatic injuries can occur with blunt trauma chest in 1–7 % of patients. Retrospectively for last 3 years all cases blunt trauma chest admitted to surgery were reviewed and a study of cases of diaphragmatic rupture was done. We analysed 496 patients of blunt trauma chest retrospectively for period of three years. Nine patients have diaphragmatic injuries, all were males, six presented acutely three were chronic. In six patients laparotomy was done, four subcostal and two midline incisions were preferred. In chronic cases thoracotomy was done. Left sided injury predominates and rib fractures are most common associated finding. Diagnosis in majority of cases is made by Computerised tomography scan. Subcostal incision may be used in patients with isolated diaphragmatic injury in acute presentation while thoracotomy is preferred in late cases. Most common morbidity is pulmonary complications